AKUNTANSI, KEKUASAAN, DAN TATA KELOLA HARGA BARANG DAN JASA SEKTOR KEHUTANAN: PERSPEKTIF SOSIOLOGI AKUNTANSI KAWASAN - Buata, Dita Aulia; Niswatin; Amaliah, Tri Handayani (Sebi : Studi Ekonomi dan Bisnis Islam, 2025)
This study aims to examine the role of accounting practices in shaping the governance of goods and services pricing in the forestry sector by adopting a regional sociology of accounting perspective. This study is grounded in the view that forestry prices are not merely the result of technical calculations, but are socially constructed through accounting practices and power relations embedded within institutional contexts. The study employs a literature review method, using thematic analysis to identify patterns and mechanisms that shape forestry price governance. The findings indicate that accounting practices actively frame forestry pricing through cost measurement, economic valuation, and reporting mechanisms that are institutionally legitimized. These practices represent and reproduce power relations among regional actors, particularly the dominance of the state and formal institutions, while also functioning as mechanisms of legitimacy that normalize forestry pricing policies as rational and objective, despite their potential to obscure social inequalities and ecological impacts. This study makes a conceptual contribution by positioning accounting as a power-laden social practice in understanding forestry price governance, thereby extending accounting research toward a more critical and context-sensitive perspective.